2014
DOI: 10.1139/cjp-2013-0608
|View full text |Cite
|
Sign up to set email alerts
|

Probing the exciton distribution in organic light-emitting diodes using long-range energy transfer

Abstract: We present a technique to probe the exciton distribution in organic light-emitting diodes. Our method involves strategically inserting sensing layers at different locations in proximity to the emissive zone. In contrast to typical sensing layers that act as a probe of the local exciton density, the sensing layers reported here use long-range energy transfer to probe a large area around the sensing layer. We highlight the importance of material selection, such that exciton distribution could be probed without i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Three consecutive steps of the energy transfer process of UEMLs is included: 1) pumping electrons in the ground state to electrons in the CT state (exciton generation; T 0 ∼100 fs), 2) Förster and Dexter energy transfer to UEMLs (energy transfer; τ 1 ∼100 ps), and 3) luminescence of UEMLs (relaxation luminescence; τ 2 ∼100 ns), with a distinguishing time scale is described with the energy structure of different organic interfaces in Figure 2 . ( Ingram et al, 2014 ; Menke and Holmes, 2014 ; Gould et al, 1994 ). The energy level diagrams of organic heterojunction interfaces are also exhibited in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three consecutive steps of the energy transfer process of UEMLs is included: 1) pumping electrons in the ground state to electrons in the CT state (exciton generation; T 0 ∼100 fs), 2) Förster and Dexter energy transfer to UEMLs (energy transfer; τ 1 ∼100 ps), and 3) luminescence of UEMLs (relaxation luminescence; τ 2 ∼100 ns), with a distinguishing time scale is described with the energy structure of different organic interfaces in Figure 2 . ( Ingram et al, 2014 ; Menke and Holmes, 2014 ; Gould et al, 1994 ). The energy level diagrams of organic heterojunction interfaces are also exhibited in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Long-range coupling of electron-hole pairs in spatially separated electron-donating and electron-accepting molecules as long as 10 nm spacer layers is reported, which is similar to type B exhibited in Figure 1B . ( Ingram et al, 2014 ; Ingram et al, 2016 ; Nakanotani et al, 2016 ). However, why the interface of the exciplex produces these positive results to the UEML and the origin of the undoped UEML within interface exciplexes is still unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…We placed a layer of C 60 molecules, close to the emissive zone and measured the fraction of excitons captured by this layer [16] . Any excitons captured by the C60 rapidly decay non-radiatively, thus simulating other non-radiative quenching centers that can occur in regular devices.…”
Section: Elimination Of Exciton Quenchingmentioning
confidence: 99%
“…This is because the transition to ground state from excited triplet states is not formally allowed since spin is not conserved in the transition. 22 Any excitons captured by C 60 rapidly decay nonradiatively, thus simulating other nonradiative quenching centers that can occur in regular devices. Since the radiative triplet to ground-state transition can occur and does so in many cases at a rate much greater than the nonradiative rate, long-range energy transfer via a Förster mechanism becomes possible.…”
Section: Long-range Quenching By Nonradiative Centersmentioning
confidence: 99%
“…22 configurations are depicted in Fig. We have shown that contrary to conventional wisdom in the field, many layers are not necessary to achieve high-efficiency devices, but rather reduce the device efficiency through exciton quenching and loss of charge balance due to charge carriers built up at interfaces.…”
Section: Simple Device Structurementioning
confidence: 99%